تشكّلات النّص الأسطوري في قصص "جنّية البحر" لجميلة زنير - بن خروف, سماح (جامعة الوادي - University of Eloued, 2020)
إنّ ما يشجّع كاتب القصّة القصيرة على الغرْف من الأساطير العريقة هو ما تحتويه من خصائص الحكي كالعقدة والأحداث، وبعض الخصائص السّردية التي جعلتها أكثر التصاقا بالفنون النّثرية السّردية، ومثلما سطّرت الأساطير في القرون الأولى، وأضْحت نصوصا مقدّسة بات لزاما على الفنون الأدبية حاضرا ومستقبلا أن تحفظ هذا التّراث الثّري مادامت تكتب عن الإنسان للإنسان، فإنّ كلّ المتعلقات المحيطة به تستلزم أن تتجسّد، وتحيط بأطوار التّاريخ بمصاغ قصصي مزوّد بحقائق وطقوس وظواهر طبيعية تستدعي التأمّل والتّفسير. الكلمات المفتاحية: التشكّلات، الأسطورة،القصة، القصة القصيرة، الشّخصية الأسطورية. Abstract: What encourages the short story writer on tacking Of ancient legends It is the contents of the storytelling like knots and events, and some Narrative characteristics Which made it more closely related to narrative prose arts, Just as legends were written in the early centuries, It became sacred texts It is imperative for the present and future literary arts to preserve this rich heritage As long as you write about man to man, All the things surrounding him must be embodied, It is surrounded by phases of history with anecdotal writings Provided with facts, rituals and natural phenomena that call for reflection and interpretation. key words: : Myth,story, short story, mythical character
مقال
Keywords: التشكّلات، الأسطورة،القصة، القصة القصيرة، الشّخصية الأسطورية.